Acute Cerebral Ischemia Increases a Set of Brain-Specific miRNAs in Serum Small Extracellular Vesicles - Zhou, Xin; Xu, Chenxue; Chao, Dachong; Chen, Zixin; Li, Shuyuan; Shi, Miaomiao; Pei, Yuqiang; Dai, Yujuan; Ji, Juling; Ji, Yuhua; Ji, Qiuhong (Frontiers in Molecular Neuroscience, 2022)
Small extracellular vesicles (sEVs) miRNAs are promising diagnosis and prognosis biomarkers for ischemic stroke (IS). This study aimed to determine the impact of IS on the serum sEVs miRNA profile of IS patients and a transient middle cerebral artery occlusion (tMCAO) mouse model. Small RNAseq was used to define the serum sEVs miRNA profile in IS patients and healthy controls (HC), and tMCAO mice and sham controls. Among the 1,444 and 1,373 miRNAs identified in human and mouse serum sEVs, the expression of 424 and 37 miRNAs was significantly altered in the IS patients and tMCAO mice, respectively (| Log2FC| ≥ 1, p < 0.01). Notably, five of the top 25 upregulated miRNAs in IS patients were brain-specific or enriched, including hsa-miR-9-3p, hsa-miR-124-3p, hsa-miR-143-3p, hsa-miR-98-5p, and hsa-miR-93-5p. Upregulation of these four miRNAs was further validated by qPCR. Nine of the 20 upregulated miRNAs in tMCAO mice were also brain-specific or enriched miRNAs. Temporal analysis indicated that the dynamics of mmu-miR-9-5p, mmu-miR-124-3p, mmu-miR-129-5p, and mmu-miR-433-3p were closely correlated with the evolution of ischemic brain injury, as their expression increased at 0.5 days after the onset of ischemia, peaked at day 1 or 3, and returned to normal levels at day 7 and 14. Notably, with the exceptions of mmu-miR-128-3p, the expression of the other eight miRNAs in the mouse serum sEVs was unaffected in the lipopolysaccharide (LPS)-induced neuroinflammation model. Together, in this study, we provided a comprehensive view of the influences of IS on the serum sEVs miRNA profile of IS patients and tMCAO mice and demonstrated the increment of a set of brain-specific miRNAs in serum sEVs after acute cerebral ischemia, which could be promising candidates directly reflecting the ischemic brain injury.